2019
DOI: 10.1002/asia.201901365
|View full text |Cite
|
Sign up to set email alerts
|

“Inverted” Deep Eutectic Solvents Based on Host‐Guest Interactions

Abstract: Herein, the concept of “inverted” (the mode “molecules mainly interact with cations”) deep eutectic solvents (DESs) is proposed. A strategy to form inverted DESs by host‐guest interactions was developed, and thus numerous DESs could be designed and formed by a combination of host and guest molecules. These liquids are expected to be used as nonaqueous electrolytes in potassium‐ion batteries or other fields for further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Depending on the character of the hydrogen bond acceptor (HBA) and the hydrogen bond donor (HBD), interactions such as hydrogen bonding, van der Waals interactions, or π–π stacking occur. Recently, novel eutectic systems, namely, eutectic molecular liquids (EMLs), were defined, and several other noncovalent interactions were identified, including not only hydrogen bonding and π–π stacking but also σ-hole (halogen, pnicogen, and tetrel bonds), π-hole, κ-hole, and μ-hole bonding interactions. , There is a huge interest in composing DESs with new and interesting properties as well as in explaining the structure–activity relationship and the interactions occurring between different HBAs and HBDs. The most valuable feature of DESs seems to be the possibility of obtaining almost unlimited numbers of tailor-made solvents by selecting appropriate HBDs and HBAs. Additionally, many DESs (also named natural deep eutectic solvents, NADESs) are bioderived, green, biocompatible, biodegradable, and nontoxic chemicals, unlike classic solvents (including solvents belonging to volatile organic compounds, VOCs) or some ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the character of the hydrogen bond acceptor (HBA) and the hydrogen bond donor (HBD), interactions such as hydrogen bonding, van der Waals interactions, or π–π stacking occur. Recently, novel eutectic systems, namely, eutectic molecular liquids (EMLs), were defined, and several other noncovalent interactions were identified, including not only hydrogen bonding and π–π stacking but also σ-hole (halogen, pnicogen, and tetrel bonds), π-hole, κ-hole, and μ-hole bonding interactions. , There is a huge interest in composing DESs with new and interesting properties as well as in explaining the structure–activity relationship and the interactions occurring between different HBAs and HBDs. The most valuable feature of DESs seems to be the possibility of obtaining almost unlimited numbers of tailor-made solvents by selecting appropriate HBDs and HBAs. Additionally, many DESs (also named natural deep eutectic solvents, NADESs) are bioderived, green, biocompatible, biodegradable, and nontoxic chemicals, unlike classic solvents (including solvents belonging to volatile organic compounds, VOCs) or some ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Deep eutectic solvents (DESs) are promising absorbents for toxic gases capture . Two or more constituents exist in DESs via hydrogen bonds between hydrogen-bonding acceptor (HBA) and hydrogen-bonding donor (HBD), halogen bonds, or pi–pi interaction, making the melting points of DESs lower than those of individuals. Components of DESs are colorful, which could be cheap and biodegradable; therefore, DESs also possess these favorable merits.…”
Section: Introductionmentioning
confidence: 99%
“…DESs with high purity can be easily prepared by mixing hydrogen bond donors (HBDs) and hydrogen bond acceptors (HBAs), which may contain two or more constituents, and does not require further purification, therefore simplifying the processes. The interactions between the constituents can be hydrogen bonds, halogen bonds, or Pi-Pi interactions that cause the melting point of synthesized DES to be significantly reduced and lower than any of the individual component [20][21][22]. Abbott et al [23] reported the first example of DES through mixing choline chloride (ChCl) with urea (UE), and then Zhu et al [24] reported that ChCl:UE DES can effectively catalyze the reactions of CO 2 and epoxides.…”
Section: Introductionmentioning
confidence: 99%